2017
DOI: 10.14295/oh.v23i1.915
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do potencial fitorremediador de crisântemo em solo com excesso de cobre

Abstract: Minimizing the harmful effects of copper (Cu) in the soil, using plants are slow and gradual, requiring the identification of species with fitorremediativa fitness for this process. Thus, the present work had as objective to evaluate the cultivation of chrysanthemum cv. Dark Fiji in soil added with Cu as promising phytoremediation. The experiment was conducted in the period from July to December 2014, in the greenhouse of the Floriculture UFSM. In a completely randomized experimental design, with five treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…em solo com excesso de Cu não observaram danos fitotóxicos nas plantas estudadas. Em contrapartida, Menegaes et al (2017a;2017b) verificaram que as espécies de Zantedeschia spp. e Dendranthema grandiflora Tzevelev cv.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…em solo com excesso de Cu não observaram danos fitotóxicos nas plantas estudadas. Em contrapartida, Menegaes et al (2017a;2017b) verificaram que as espécies de Zantedeschia spp. e Dendranthema grandiflora Tzevelev cv.…”
Section: Resultsunclassified
“…Zancheta et al (2011) relatam que a alta retenção de Cu nas raízes é um indicativo de tolerância da planta ao cultivo em solos com excesso deste elemento. Menegaes et al (2017a) verificaram em estudos com a espécie de Zantedeschia spp., cultivada em solo com alto teor de Cu, o acúmulo deste elemento nos tubérculos com baixa translocação para a parte aérea, afetando negativamente o seu desenvolvimento e floração.…”
Section: Resultsunclassified
“…In addition, it showed a high tendency for the phytostabilization of Ni and As and the phytoextraction of the metals Ba, Cd, Cu, Ni, Se and Zn, present in the commercial substrate. Subjecting chrysanthemums (D. grandiflora) to Cu contaminated soil, Menegaes et al (2017) observed that this species showed tolerance to high rates of this metal and stands out for its ability to retain this element in its roots. However, the authors point out that the aesthetic quality was affected, which jeopardizes its commercial value.…”
Section: Ornamental Plants In Phytoremediationmentioning
confidence: 99%
“…Cu-stress caused a small decrease in the efficiency of photosystem 2 photochemistry, but its primary effect was on growth [16]. Copper ions reduce the quality of ornamental plants [17]. The aim of this study was to assess phytotoxicity of copper for Chrysanthemum carinatum and lawn grass.…”
Section: Introductionmentioning
confidence: 99%